Capacity, equity, empowerment and sustainability Focusing on Gawad Kalinga's Gawad Kabuhayan at Brgy. Naparaan, Salcedo, Eastern Samar. - Odivilas, Thea Amor O. (Thea Amor O. Odivilas, 2009)
This study intended to find out the capacity, equity, empowerment and sustainability: Focusing in Gawad Kalinga's Gawad Kabuhayan at Brgy. Naparaan, Salcedo, Eastern Samar. This study proved to be useful in evaluating how involved and empowered the GK residents are. This assessed how effective Gawad Kanuhayan is as a tool for empowerment, development, and democratization.